2018
DOI: 10.4314/wsa.v44i1.01
|View full text |Cite
|
Sign up to set email alerts
|

The effect of anaerobic baffled reactor effluent on nitrogen and phosphorus leaching from four soils in a laboratory column experiment

Abstract: Leaching of nitrogen and phosphorus from soil columns during application of anaerobic baffled reactor effluent was evaluated. The soils used were from Inanda (Ia), Cartref (Cf), and Sepane (Se) forms, and a silica sand (SS). Each was packed into duplicate columns (103 mm internal diameter; 200 mm length), four each for up-flow and down-flow leaching. Effluent was delivered continuously for 6, 8 and 35 days at high (32 mm·h ) rates, respectively. At each flow rate, 9 pore volumes were collected. Leachates were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The study was designed and modified from the studies conducted by Adhanom et al (2018) and Das et al (2020). 27,28 In brief, three cylindrical glass columns with an internal diameter of 5 cm and a length of 70 cm fitted with a nozzle for the elution of water were used. The columns were designated as column A (commercial urea), column B (bare NU), and column C (NUCNC).…”
Section: Soil Column Studiesmentioning
confidence: 99%
“…The study was designed and modified from the studies conducted by Adhanom et al (2018) and Das et al (2020). 27,28 In brief, three cylindrical glass columns with an internal diameter of 5 cm and a length of 70 cm fitted with a nozzle for the elution of water were used. The columns were designated as column A (commercial urea), column B (bare NU), and column C (NUCNC).…”
Section: Soil Column Studiesmentioning
confidence: 99%
“…The high canopy cover Golden Delicious/Golden Delicious Reinders orchards were harvested mid-to end-March while the Cripps' Pink (and its mutations) orchards were harvested in late April for each of the seasons. It is evident from Table 5 that there were no significant differences between the two cultivars in the contribution of the March to end-of-season (June) transpiration, suggesting that there was no incremental water use by the canopy cover during the growing season was the main driver of water use in apple orchards, although other studies, e.g., Naor et al (1997) suggested that in similarly sized mature canopies, crop load was the main factor determining apple orchard water use. Therefore, growers should carefully manage the canopy size to reduce orchard water use.…”
Section: Discussionmentioning
confidence: 86%
“…Nitrogen enters the shallow groundwater in numerous organic and inorganic forms and, due to their high solubility, is easily transported from septic and sewage tanks to the deeper aquifer zones, thus contaminating the aquifers (Simmons et al, 1992;Heatwole andMcCray 2007, Moodley et al, 2017;Adams et al 2019). Inappropriate wastewater treatment has led to widespread N pollution of aquatic systems, not only in the less-developed areas of the world, but in developed areas as well (Fantong et al, 2013;Gooddy et al, 2014;Benrabah et al, 2016, Robertson et al, 2016Adhanom et al, 2018).…”
Section: Introductionmentioning
confidence: 99%